Increasing the efficiency of wind turbines - Varol, A; Ilkiliç, C; Varol, Y (Elsevier Science Bv, 2001)
The importance of clean energy sources was realised rapidly after the negative effects of the pollution caused by generators on the environment became clear. Wind energy is a clean and renewable energy source whose applications exist worldwide. Some countries Changed their national energy forward planning for renewable clean energy projects. In developed countries some researchers have worked on developing new kinds of wind turbines in order to produce a part of their power from renewable wind energy. The rotational speed of the wind blades can be increased using steering aerofoils surrounding the blades. A prototype of this wind turbine has been made in the laboratory; a ventilator whose flow rate is variable generates the 'wind'. The blade profiles are designed using the theory of aerodynamics. The steering aerofoils are fixed surrounding the wind blades at an optimum distance. The number of the aerofoils and the angle of inclination (tilt) of the foils can be changed. In the experiment the ambient conditions are held constant. Because of the optimum adjustment of the distance and angle of the aerofoils the rotational speed of the blades can be increased by 32% on the experimental device. In this paper the theoretical and experimental results will be discussed. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: wind energy; efficiency; aerofoils